Deformation behavior and microstructural evolution of directionally solidified TiAlNb-based alloy during thermo-compression at 1373–1573 K. (5th November 2015) - Dong, Shulin; Chen, Ruirun; Guo, Jingjie; Ding, Hongsheng; Su, Yanqing; Fu, Hengzhi
Abstract: Alloy Ti44Al6Nb1.0Cr2.0V0.15Y0.1B is newly designed and melted by vacuum consumable melting method, and is then prepared by cold crucible directional solidification (CCDS) technology. Thermo-compression experiment is carried out on CCDS billets at 1373–1573 K. Experimental results show that, when compressing direction (CD) is perpendicular to columnar grains, higher deformation active energy of Q = 689.8 kJ/mol can be acquired which means excellent creep resistance in radial direction; the microstructural evolution with different lnZ parameters is investigated by electron back scattering diffraction and the deformation mechanism is discussed; the ordering temperature of B2/β phase is deduced to be in the range of 1200–1250 °C. When the CD is parallel to the columnar grains, a much higher peak stress is acquired which means more excellent creep resistance in the axial direction; the shearing deformation feature is presented and the schematic of deformation mechanism is given. Graphical abstract: Highlights: Deformation resistance is excellent for directionally solidified TiAl alloy. Ordering temperature of B2 phase is in the range of 1373–1573 K. Shear deformation feature is exhibited as axial compression at 1373–1573 K.